Large-area MACE Si nano-inverted-pyramids for PERC solar cell application. (August 2019) - Huang, Z.G.; Gao, K.; Wang, X.G.; Xu, C.; Song, X.M.; Shi, L.X.; Zhang, Y.; Hoex, B.; Shen, W.Z.
Highlights: Prepare the well-organized and uniformity nano-inverted-pyramids (NIPs) textures by MACE technique. NIPs possess better light-trapping superiorities over the wavelength range of 300–600 nm. The simulated NIPs-PERC solar cell possesses an efficiency of 22.09%, which is 1.4% relatively higher than that of the traditional PERC. NIPs-PERC module can yield a peak power of 310 W which is 8 W higher than a traditional PERC module. Abstract: Silicon (Si) nanostructures are regarded as a competitive candidate for the front texture of future high-efficiency Si solar cells owing to their excellent light-trapping properties. In this paper, we present nano-inverted-pyramids (NIPs) textures on the surface of Cz Si wafer with an area of 156 × 156 mm 2 fabricated by employing the metal-assisted chemical etching (MACE) technique. The optical properties of the surface are investigated in detail before and after the application of a SiOx /SiNx antireflection coating. A passivated emitter and rear contact (PERC) solar cell with NIPs (NIPs-PERC) is analyzed at the cell as well module level using simulation. The simulation results indicate that the NIPs-PERC solar cell possesses a higher efficiency (η) of 1.4% relatively than that of the traditional PERC solar cell, benefiting from a significant better reflection performance in both the short as well as long wavelength range. Furthermore, simulations show that a 60-cell module with NIPs-PERC solar cells can yield a peak power of 310 W which is 8 W higher than a traditional PERC module. The novel NIPs-PERC solar cell shows high potential for mass production and opens a broad way for the application of NIPs textures to other high-performance solar cells.